PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Septa Maidi Putri; Edy Swasono; Imam Baehaki (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
The aimed of this study was to determine the effect of organizational culture and leadership style on employee performance through job satisfaction as an intervening variable. This type of research used quantitative research. Data collected used questionnaires and documentation with a total sample of 108 people. Data analysis techniques used are descriptive analysis and path analysis. The results showed that 1) Organizational Culture signifies significant effect on employee performance. 2) Leadership style has a significant effect on employee performance. 3) Job satisfaction has a significant effect on employee performance. 4) Organizational culture has a significant effect on job satisfaction. 5) Significant influential leadership style on job satisfaction. 6) Job satisfaction is an intervening variable between organizational culture and employee performance because the value of indirect influence is greater than direct influence. 7) Job satisfaction is an intervening variable between leadership style on employee performance because the value of indirect influence is greater than direct influence.